The inundation stela of Sebekhotpe VIII - John Baines (1974)
A fragmentary stela found in the third pylon at in the temple of Amon-Re at Karnak in Egypt is dated to year 4 of Sebekhotpe VIII, 4 shomu, the epagomenal days. The text on the verso mentions a great inundation, which flooded the weskhet-hall of the temple. The king went to the temple (probably to take precautions) and was seen wading in the water. The coincidence of date and flood allowed a full re-enactment of creation: by wading in the flood in the temple the king was coming as near as he could to imitating the actions of the creator god. the scene on the recto shows the king wearing the flat cap with uraeus and two tall feathers and thus relates him rather closely to Amon-Re.